Holding on to reality : the nature of information at the turn of the millennium - Borgmann, Albert 1937- (University of Chicago Press, 1999)
'Holding on to Reality' is a history of information, from its inception in the natural world to its role in the transformation of culture to the current Internet mania and its attendant assets and liabilities. Drawing on the history of ideas, the details of information technology, and the boundaries of the human condition, Borgmann illuminates the relationship between things and signs, between reality and information.